2018
DOI: 10.1136/jmedgenet-2018-105262
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in plasmalemma vesicle-associated protein cause severe syndromic protein-losing enteropathy

Abstract: Our findings validate mutations as a cause of syndromic PLE. Prenatal anomalies, severe PLE and syndromic features may guide the diagnosis of this rare disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
2
18
0
Order By: Relevance
“…Disease onset in the proband (III-1) was in early adulthood, whereas patient IV-2 had childhood onset of PLE. Moreover, patient IV-2 had severe hypertriglyceridaemia, with plasma concentrations 16-fold higher than normal range, similar to the first reported PLVAP -null patient,7 while the proband had normal serum triglycerides; triglyceride levels were not reported in Broekaert et al 8 This phenotypic variability suggests the presence of other modifying factors. Review of the proband’s WES results revealed that he carries a heterozygous nonsense variant in CETP (NM_000078.2:c.544C>T;p.Gln182*), which encodes the cholesteryl ester transfer protein, while patient IV-2 is wild type.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Disease onset in the proband (III-1) was in early adulthood, whereas patient IV-2 had childhood onset of PLE. Moreover, patient IV-2 had severe hypertriglyceridaemia, with plasma concentrations 16-fold higher than normal range, similar to the first reported PLVAP -null patient,7 while the proband had normal serum triglycerides; triglyceride levels were not reported in Broekaert et al 8 This phenotypic variability suggests the presence of other modifying factors. Review of the proband’s WES results revealed that he carries a heterozygous nonsense variant in CETP (NM_000078.2:c.544C>T;p.Gln182*), which encodes the cholesteryl ester transfer protein, while patient IV-2 is wild type.…”
Section: Discussionsupporting
confidence: 76%
“…(B) Sequence chromatogram of the c.101T>C variant in a homozygous patient and heterozygous parent. (C) Structure of the PLVAP gene (top) and PLVAP (PV-1) protein (bottom), denoting the location of reported variants: the c.101T>C;p.Leu34Pro missense variant identified in this study, and the nonsense pathogenic variants described previously by Elkadri et al 7 and Broekaert et al 8 both occurring in the third exon and truncating the protein in the second coiled-coil domain. TM, transmembrane; PRR, proline-rich region.…”
Section: Methodssupporting
confidence: 73%
“…Endothelial diaphragms are ~40‐80 nm subcellular structures critical for life . They occur in endothelial cells (EC) of capillaries and venules in select vascular beds (reviewed in).…”
Section: Introductionmentioning
confidence: 99%
“…PLVAP knockdown in human or mouse cells results in endothelial diaphragms disappearance. Similarly, PLVAP deletion in mice or nonsense mutations in humans lead to no diaphragm formation. The in vivo loss of diaphragms results in failure of endothelial barrier function.…”
Section: Introductionmentioning
confidence: 99%
“…Exome sequencing of the index patient was performed using the Illumina HiSeq (Illumina, San Diego, CA, USA) 2,000 sequencing instrument with 2 Â 76 bp as described earlier. 11 Exome sequencing resulted in > 81 million of mapped unique sequences with a mean coverage of 70, that is, Â20 coverage for 92.1% of the target sequences. The Cologne Center for Genomics VARBANK pipeline v.2.24 (Cologne Center for Genomics, Cologne) (https://varbank.ccg.uni-koeln.de/) was used for read mapping, variant calling, and variant filtering.…”
Section: Clinical Case Presentationmentioning
confidence: 99%